HUBUNGAN TINGKAT STRES DENGAN OLAHRAGA RUTIN MAHASISWA PROGRAM STUDI SARJANA KEDOKTERAN DAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Ummaiya, Fadilla; Tirtayasa, Ketut; Griadhi, I Putu Adiartha (E-Jurnal Medika Udayana; Vol 11 No 3 (2022): E-Jurnal Medika Udayana, 2022)
ABSTRACT The transition from high school to tertiary education requires adaptation, because college is the toughest period during education. Some studies say that Medical Education is the toughest field of study that creates pressure. The pressure that arises is increasing and continues to cause anxiety. The impact of anxiety is stress. One of the efforts to increase stress immunity is by exercising. Exercise is part of one's life and is very useful to balance life, especially for students, by exercising one can reduce the impact of stress physiologically and psychologically. The purpose of this study was to determine the relationship between stress levels and routine exercise among students. This study is an observational analytic study with a cross sectional method using a stress level questionnaire and a sports questionnaire and totaling 80 collage students from the Undergraduate Medicine and Professional Doctor Study Program, Faculty of Medicine, Udayana University, class of 2019 as a respondents. Conducted in April-July 2020 via google form with variable independent of routine exercise and variable dependent stress level and variable confounding of residence, academic achievement, and gender. Based on the results of the Chi-Squere test , it showed that no relationship between stress levels and exercise (p = 0.109). It can be concluded that it has no relationship, so it is necessary to do further research on stress both in relation to routine exercise and other factors. Keywords: Stress, exercise, medical students